A Tentative Exploration into the Amount and Equivocality of Information Processing in Organizational Work Units - Daft, Richard L.; Macintosh, Norman B. (Administrative Science Quarterly, 1981)
Richard L. Daft, Norman B. Macintosh, A Tentative Exploration into the Amount and Equivocality of Information Processing in Organizational Work Units, Administrative Science Quarterly, Vol. 26, No. 2 (Jun., 1981), pp. 207-224